2017
DOI: 10.1111/bjd.15118
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year incidence of contact dermatitis in a prospective cohort of healthcare workers in Trieste hospitals (North East of Italy) 2004-2013

Abstract: N/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Larese et al 11 in Italy analysing only glove-related OCD in 2000-2009 found an incidence rate of 23.9 and 25.0 cases per 10 000 workers/year for ICD and ACD, respectively, and analysing all OCD in 2004-2013 an incidence rate of 45 cases for 10 000 workers/year. 12 OCD incidence was higher for nurses (61.4 cases per 10 000 workers/year) and lower for medical doctors (15.9 cases for 10 000 workers/year). 12 Other studies calculated the incidence of OCD using registers of occupational diseases, finding values ranging between 1.0 to 13.8 cases per 10 000 workers/year considering different countries and occupations, higher for dentists (11 cases per 10 000/ year) and dental technicians (13.8 cases per 10 000/year) with a declining trend in years considered.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…Larese et al 11 in Italy analysing only glove-related OCD in 2000-2009 found an incidence rate of 23.9 and 25.0 cases per 10 000 workers/year for ICD and ACD, respectively, and analysing all OCD in 2004-2013 an incidence rate of 45 cases for 10 000 workers/year. 12 OCD incidence was higher for nurses (61.4 cases per 10 000 workers/year) and lower for medical doctors (15.9 cases for 10 000 workers/year). 12 Other studies calculated the incidence of OCD using registers of occupational diseases, finding values ranging between 1.0 to 13.8 cases per 10 000 workers/year considering different countries and occupations, higher for dentists (11 cases per 10 000/ year) and dental technicians (13.8 cases per 10 000/year) with a declining trend in years considered.…”
Section: Resultsmentioning
confidence: 83%
“…12 OCD incidence was higher for nurses (61.4 cases per 10 000 workers/year) and lower for medical doctors (15.9 cases for 10 000 workers/year). 12 Other studies calculated the incidence of OCD using registers of occupational diseases, finding values ranging between 1.0 to 13.8 cases per 10 000 workers/year considering different countries and occupations, higher for dentists (11 cases per 10 000/ year) and dental technicians (13.8 cases per 10 000/year) with a declining trend in years considered. [13][14][15][16]…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations